WASTE MANAGEMENT STRATEGIES IN ADO-EKITI METROPOLIS OF EKITI STATE, NIGERIA - Akindutire, Isaac Olusola; Alebiosu, Eunice Oluyemisi (European Scientific Journal, ESJ, 2013)
This study examined waste management techniques in Ado-Ekiti metropolis of Ekiti state, Nigeria. Four hypotheses were formulated to guide the study. Descriptive survey research design was used and 1,200 respondents were randomly sampled in different parts of the city. A questionnaire was used to collect the data for the study. The data were analyzed using percentage and chi-square (X2). The result revealed that, the people in Ado-Ekiti metropolis mostly dispose their waste materials through open dumping. It was also discovered that there is significant relationship between the people’s level of education, age and financial status and waste management techniques. However, the result indicated that there is no difference in the techniques used by people at different sections of the town to dispose their waste. Based on the findings, it was recommended that, illiteracy level should be reduced; government should intensify enlightenment campaign; provide more waste disposal containers; more toilets should be provided at home and public places such as, markets, schools, government universities; and people should be enlightened on waste recycling and conversion for further utilisation.